2014
DOI: 10.1002/gps.4088
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of duloxetine in the treatment of older adult patients with generalized anxiety disorder: a randomized, double‐blind, placebo‐controlled trial

Abstract: ObjectiveThis was a flexible-dosed study to evaluate the efficacy and safety of duloxetine 30–120 mg once daily in the treatment of generalized anxiety disorder (GAD) in older adult patients.MethodsPatients with GAD, who were at least 65 years of age, were randomly assigned to double-blind treatment with either duloxetine (N = 151) or placebo (N = 140). The primary efficacy measure was the Hamilton Anxiety Rating Scale (HAM-A) total score, and the primary endpoint was at week 10. Global functioning was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 42 publications
(56 reference statements)
0
35
0
Order By: Relevance
“…Twenty-two placebo-controlled RCTs were deemed eligible for further inclusion in metaanalyses. [10][11][12][15][16][17][19][20][21][22][23][24][25][26][27][29][30][31][32][33] Of the RCTs, included trials investigated drugs used for urinary frequency and incontinence (ATC code G04BD) (n = 13), 12,15,16,19,20,22,[29][30][31][32][33] antidepressants (N06A) (n = 6), 10,11,21,[25][26][27] and psycholeptics (N05) (n = 3). 17,23,24 Statistical heterogeneity was substantial across the trials assessing drugs used for urinary frequency and incontinence (I 2 = 62%).…”
Section: Metaanalysismentioning
confidence: 99%
“…Twenty-two placebo-controlled RCTs were deemed eligible for further inclusion in metaanalyses. [10][11][12][15][16][17][19][20][21][22][23][24][25][26][27][29][30][31][32][33] Of the RCTs, included trials investigated drugs used for urinary frequency and incontinence (ATC code G04BD) (n = 13), 12,15,16,19,20,22,[29][30][31][32][33] antidepressants (N06A) (n = 6), 10,11,21,[25][26][27] and psycholeptics (N05) (n = 3). 17,23,24 Statistical heterogeneity was substantial across the trials assessing drugs used for urinary frequency and incontinence (I 2 = 62%).…”
Section: Metaanalysismentioning
confidence: 99%
“…Duloxetine is FDA-approved for GAD and had and has similar efficacy and side effect profile to SSRIs [40]. Additionally, blood pressure effects were not as significant as with venlafaxine [41].…”
Section: Serotonin and Norepinephrine Reuptake Inhibitors (Snris)mentioning
confidence: 99%
“…A total of 278 studies were initially identified through the electronic search. First pass screening eliminated, leaving 30 studies (Stahl et al ., ; Koponen et al ., , ; Allgulander et al ., , ; Hartford et al ., , ; Russell et al ., , ; Davidson et al ., ; De Berardis et al ., ; Hoschl and Svestka, ; Norman and Olver, ; Pollack et al ., ; Rynn et al ., ; Trivedi et al ., ; Katzman, ; Kornstein et al ., ; Nicolini et al ., ; Simon et al ., , ; Pangallo et al ., ; Wu et al ., , ; Bodkin et al ., ; Piero and Locati, ; Sheehan et al ., ; Karaiskos et al ., ; Mavranezouli et al ., ; Alaka et al ., ) were considered potentially relevant for further inspection. After screening the full text, seven randomized controlled trials (RCTs) (Hartford et al ., ; Koponen et al ., ; Davidson et al ., ; Rynn et al ., ; Nicolini et al ., ; Wu et al ., ; Alaka et al ., ) ( n = 2,674) were available for meta‐analyses.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies were reported as double‐blind RCTs, but only two (Nicolini et al ., ; Alaka et al ., ) explicitly stated the method of random sequence generation. Poor study quality was associated with inadequate or unclear reporting of blinding, randomization protocols, or support by medical company.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation